IKN between symbol and struggle: Governmental framing and public perception on IKN in East Kalimantan - Arifin, Muhammad Bahri; Rahayu, Famala Eka Sanhadi; Gunawan, Sindy Alicia (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study investigates the ideological and discursive tensions surrounding Indonesia’s new capital city (IKN) project in East Kalimantan. While the government frames IKN as a “smart forest city” symbolizing national progress and ecological harmony, local communities—particularly indigenous groups—report environmental degradation and cultural displacement. Using Ecological Discourse Analysis (EDA) and framing theory, the research compares official narratives from presidential speeches and planning documents with grassroots perspectives documented by NGOs. The findings reveal a discursive gap that raises concerns about greenwashing and symbolic power in state-led development. This study contributes to ecolinguistics by highlighting how language mediates environmental ideology and public perception in contested urban transformations.